Identifikasi Tingkat Kekumuhan di Kelurahan Mandala Distrik Jayapura Utara Kota Jayapura - Soleman Patai; Deasy Widyastomo; Marulitua Manalu (Fakultas Teknik Universitas Cenderawasih, 2024)
This research discusses the identification of slum level in Mandala Sub-district, North Jayapura District, Jayapura City. The research employs a qualitative descriptive approach with primary data obtained from observations, interviews, and documentation. Mandala Sub-district faces issues of development inequality and high population density, including unsuitable living conditions in its residential areas. The identification results indicate that the slum level in Mandala Sub-district falls under the category of